Population data of 21 autosomal STR loci in Malaysian populations for human identification - Rashid, MNA; Mahat, NA; Khan, HO; Wahab, RA; Maarof, H; Ismail, D; Alwi, AR; SyedHassan, SR (Springer, 2024)
The use of 21 autosomal STR loci for human identification has been gaining popularity throughout the world. It has been indicated that the forensic statistical parameters for supporting the use of 21 STR loci varied among different populations. Hitherto, such data for the diverse Malaysian populations remain unreported, rendering doubts in the court of law about its real ability for human identification in Malaysian population. Using the GlobalFiler (TM) Express PCR Amplification Kit, complete DNA profiles of 21 STR loci from buccal swabs of convicted Malaysian criminal (n = 570; 190 each for Malays, Chinese, and Indians) (by the year 2016-2017) were analyzed for their allele frequencies, exact test of Hardy-Weinberg equilibrium, observed and expected heterozygosity, power of discrimination, power of exclusion, match probability, and polymorphism information content. Most of the loci were found to be in the Hardy-Weinberg equilibrium after the Bonferroni correction. Being the most informative locus, SE33 demonstrated the highest power of discrimination and power of exclusion, indicating its usefulness to discriminate individuals. In contrast, TPOX had the lowest power of discrimination and power of exclusion, as well as being the less informative genetic locus for all Malaysian population studied here. The probabilities that two individuals would share the same DNA profiles among the Malaysian Malays, Chinese, and Indians, as well as in general Malaysian population, were 1.3713 x 10(-25), 2.8822 x 10(-25), 7.5668 x 10(-26), and 1.0385 x 10(-26), respectively. The results obtained here were found comparable with similar studies reported in other populations. Hence, its robustness for forensic human identification among the Malaysian populations is, therefore, statistically supported.